Impact of Microfinance on Women Empowerment : A Study of Rural Gujarat - Patel, Ritesh; Patel, Mitesh; Patel, Nikunj (Indian Journal of Finance, 2018)
Microfinance is considered as an important financial service in many countries. The objective of this study was to evaluate the impact of microfinance on women empowerment. The paper aimed to judge the societal transformation through strategic interventions of microfinance in rural areas. A total of 384 women staying in rural areas of Mehsana and Navsari district were surveyed. Paired t - test was performed to analyze the situation before and after women joined SHGs for women empowerment on three contexts, that is, political, social, and economic on 12 variables. Paired t - test revealed a significant difference in women empowerment indicators before and after joining SHGs. The results of binary logistic regression revealed that with the increase in duration of membership by 1 year, the probability of empowering women on grounds of economic, social, and political empowerment increased by 9%, 14%, and 11%, respectively. The study can be used to empower women on the grounds of political, social, and economic conditions. The successful implementation of microfinance could lead to societal transformation in rural areas, especially for a country like India. It was suggested that the government and non-government organizations (NGOs) can work on microfinance services to empower women.